Evidence of a continent-wide shift of episodic rainfall in Australia - Raktima Dey; Ailie J.E. Gallant; Sophie C. Lewis (Weather and Climate Extremes, 2020)
Extreme daily rainfall has intensified and become more frequent globally. However, in Australia, long-term changes in the characteristics of extreme rainfall are not well understood. Commonly used indices that examine the characteristics of rainfall rarely show statistically significant long-term historical changes in mean and extreme rainfall events. Here we use a rainfall event-based approach to study observed changes in intensity and frequency of rainfall events in Australia. This approach defines rain events as n consecutive days of rain to account for varying event duration. The intensity of a rainfall event is defined as the average of the daily accumulation of rainfall over the event duration. We find that short-duration rainfall events (1–2 day) have become more frequent and have intensified in large parts of Australia since the beginning of the 20th century. The frequency of longer duration rainfall events (3–4 day and 5–6 day) show substantial and statistically significant reductions in the south of Australia and increases in some parts of northern Australia. The frequency of rainfall events lasting >6 days has increased in the north and decreased in the south. The robust increase in short-duration episodic rainfall events across Australia and decrease in the frequency of extended episodic events imply rainfall has become more sporadic in Australia. Changes in rainfall intensities are less consistent compared to changes in frequency across the continent. We find an increase in intensity in the 1–2 and 3–4 day events, but the trends in the intensity of those events lasting >4 days are mostly not significant. Overall, changes in the characteristics of rainfall events of duration n days provide more spatially coherent results than those presented previously.